Quechua na administração da justiça em Ancash, Peru - Julca Guerrero, Félix (2025)
Within the framework of the right to one’s language as a fundamental right of every person and people, this paper analyzes the presence of Quechua in the administration of justice in Ancash (Peru) from a legal-normative perspective and its implementation. The recognition and promotion of cultural and linguistic diversity is increasingly growing and, along with this, linguistic rights are gaining fundamental importance at the normative level associated with social activism and ongoing debates in professional circles. The information was organized through documentary analysis and in-depth interviews to describe, analyze, and interpret from a qualitative approach . The results highlight the effort for a normative framework not only at the national level but also at the regional and local levels in favor of the revalorization and strengthening of Quechua through its use in the administration of justice and life in society. However, the norms are not accompanied by plans and programs with budgets and funding, which limits their implementation and progress is still minimal.